Medicinal Plants from Latin America with Wound Healing Activity: Ethnomedicine, Phytochemistry, Preclinical and Clinical Studies-A Review - Anuar Salazar-Gómez; Angel Josabad Alonso-Castro (MDPI AG, 2022)
Latin America is a multicultural region with ancient traditional medicine. There is extensive knowledge of the use of medicinal plants for wound healing in this region. Nevertheless, many of these medicinal plants lack pharmacological, toxicological, and chemical studies. This review focuses on the ethnomedicinal, phytochemical, and pharmacological (preclinical and clinical) studies of medicinal plants with wound healing activity, from Latin America. An electronic database search was conducted by consulting scientific articles and books. A total of 305 plant species with wound healing activity were recorded, based on traditional medicine. Most medicinal plants used in wound healing in Latin America are topically administered; their methods of preparation are mainly by water infusion from aerial parts. Only thirty-five percent of medicinal plants used in traditional medicine for wound healing have been experimentally validated for their pharmacological effects, and the wound healing activity of five medicinal plants has been studied in clinical trials. In all, 25 compounds (mostly terpenes and flavonoids) have been isolated from medicinal plants with wound healing activity; therefore, extensive work is necessary for a multidisciplinary approach to evaluate the wound healing effects of medicinal plants in Latin America. The mechanism of action of medicinal plants, their toxicological actions on the skin, and their bioactive compounds, have yet to be investigated. This review on the ethnomedicinal, phytochemical, and pharmacological studies, of medicinal plants from Latin America with wound healing activity, offers promising data for further studies, as well as providing new insights into their possible role in wound care.